Spontaneous Thyroid Hemorrhage Caused by Langerhans Cell Histiocytosis: A Case Report and Literature Review - Zhang, Jingying; Wang, Chengchen; Lin, Chuanshuai; Bai, Binglong; Ye, Mao; Xiang, Dapeng; Li, Zhiyu (Frontiers in Endocrinology, 2021)
Abstract Purpose: Langerhans cell histiocytosis (LCH) is a rare clonal disorder of Langerhans antigen-presenting cells. However, thyroid LCH involvement is relatively rare. We present the first case of spontaneous thyroid hemorrhage due to LCH progression and discuss the clinical features, diagnosis, and treatments of thyroid LCH in a literature review. Methods: Clinical data were collected. Previously published articles on thyroid LCH involvement were reviewed to assess the clinical features, diagnosis, and treatments for thyroid LCH. Results: A 54-year-old female presented with a multi-system LCH, affecting the uterus, liver, pituitary gland, and thyroid gland. Clinical stability was achieved after systemic chemotherapy. After 7 years of regular follow up, the patient complained of a sudden painful neck swelling and progressive dyspnea. Computed Tomography revealed bilateral goiter with hematoma, and the patient was diagnosed with spontaneous thyroid bleeding based on her clinical symptoms and radiological findings. The patient was incubated to relieve airway compromise and partial thyroidectomy was performed for definitive treatment. Pathological evaluation further confirmed the diagnosis of thyroid LCH. The patient recovered well after surgery. Conclusion: Spontaneous thyroid bleeding due to thyroid LCH progression is extremely rare. Treatments for LCH vary depending on the severity of the disease. We suggest that, for patients with multi-system LCH with thyroid lesion, long-term active surveillance of thyroid hormone concentrations, and thyroid gland volume is required. Physicians should be alert of the potentially life-threatening spontaneous thyroid hemorrhage when aggravated diffuse goiter and hypothyroidism appear. Further investigation is required to establish the guidelines for thyroid LCH treatment.